2004
DOI: 10.5006/1.3287728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Line Pipe Steel Microstructure on Susceptibility to Sulfide Stress Cracking

Abstract: The purpose of this experiment was to evaluate the effect of microstructure on sulfide stress cracking (SSC) properties of line pipe steel. Different kinds of microstructures, with chemical compositions identical to one steel heat, were produced by various thermomechanically controlled processes (TMCP). Coarse ferrite-pearlite, fine ferrite-pearlite, ferrite-acicular ferrite, and ferrite-bainite microstructures were investigated with respect to corrosion properties, hydrogen diffusion, and SSC behavior. SSC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…On the other hand, the results obtained from the present study are comparable to those reported Koh et al [30] for pipeline steels having ferrite-pearlite microstructures.…”
Section: Comparison Of the Estimated Permeation Parameters With Litersupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, the results obtained from the present study are comparable to those reported Koh et al [30] for pipeline steels having ferrite-pearlite microstructures.…”
Section: Comparison Of the Estimated Permeation Parameters With Litersupporting
confidence: 91%
“…In the past few decades, several investigations have dealt with the influence of various parameters on diffusion in pipeline steels [14,[25][26][27][28][29][30][31][32][33][34][35]. Table 1 summarises diffusion coefficients and other parameters obtained, for pipeline steels, by different authors along with other related information such as the solutions employed, exit side coating and method used for calculating the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that H 2 S originating from different processes in the oil and gas industry can accelerate the anodic and cathodic reactions of the corrosion process: iron dissolution and hydrogen evolution reaction, respectively [1][2][3][4][5][6][7][8][9][10] . Studies focusing on improving the resistance of pipeline steels to H 2 S corrosion to avoid failures during oil and gas transport have been reported [9][10][11][12][13][14] . In Brazil, the manufacture and use of high-strength low-alloy steel pipelines have been implemented in recent decades; these pipelines are nationally produced using thermomechanical controlled processing (TMCP) without accelerated cooling and fabricated using the UOE process (pressing a U-shaped pipe between two semi-circular dies to form an O-shaped pipe, then welding the pipe closed and circumferentially expanding it to obtain a highly circular shape) for the conduction of liquid and gaseous hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…The high-strength ferritic steels used in the petrochemical industry suffer frequently from hydrogen assisted cracking (HAC) problem when they are used in a sour environment containing H 2 S. [1][2][3] Atomic hydrogens which result from the reduction of H + ions dissociated from H 2 S become the hydrogen molecule by the recombination reaction (H + H → H 2 ). Since H 2 S dissolved in aqueous environment suppresses this recombination reaction, the hydrogen atoms are easily adsorbed on the steel surface and diffuse into the steel matrix.…”
mentioning
confidence: 99%